Identification Hub Genes in Colorectal Cancer by Integrating Weighted Gene Co-Expression Network Analysis and Clinical Validation in vivo and vitro - Yuan, Yihang; Chen, Ji; Wang, Jue; Xu, Ming; Zhang, Yunpeng; Sun, Peng; Liang, Leilei (Frontiers in Oncology, 2020)
Colorectal cancer (CRC) is the third leading cause of death worldwide. However, the key roles of most molecules in CRC remain unclear. This study aimed to identify key modules and hub genes associated with the pathogenesis of CRC. The data of the patients with CRC were obtained from the Gene Expression Omnibus (GEO) database and assessed by weighted gene co-expression network analysis (WGCNA), Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses performed in R. By utilizing WGCNA, several hub genes that regulate the mechanism of tumourigenesis in CRC were identified, which were associated with clinical traits. Next, we screened hub genes related to the progression of CRC authenticated by The Cancer Genome Atlas (TCGA) and Oncomine databases. Three hub genes (HCLS1, EVI2B and CD48) were identified, and survival analysis was also performed. Moreover, the results of qPCR and immunohistochemistry staining revealed that HCLS1, EVI2B and CD48 are tumour suppressor genes. Further, the functional study confirmed that over-expression of HCLS1, EVI2B and CD48 can reduce the proliferation, migration and invasion ability of CRC cells in vitro and significantly suppress CRC tumour growth in vivo. In summary, we identified three hub genes that were associated with the progression of CRC that can be applied in treatment.